Mapping the doctoral students’ experiences: A customer journey analysis - Puteri Fadzline, Muhamad Tamyez; Norhana, Mohd Aripin; Muhammad Ashraf, Fauzi; Senthil, Kumar (Malque Publishing, 2024)
Customer experience research predominantly anchors the customer journey on a specific offering, implying an inherently customer-centric perspective. To address calls for a more goal-oriented approach, this study aims to develop an educational institutional view of customer journeys from the perspective of doctoral students. In a qualitative study, nineteen doctoral students were interviewed. Two independent researchers used triple coding and thematic analysis to unpack the experiences grounded by the perspective of the self-regulation model of a behaviour feedback loop. The findings suggest two pre-journey themes: supervisor selection and personal concerns, and three during-journey themes, namely, research complexity, administrative hurdles, and personal and social support struggles. The informants had pleasant experiences during the phase of the customer journey, expressing a favourable inclination towards trust and value. Nevertheless, they had difficulties in locating appropriate supervisors as a result of insufficient organised information. Several informants have reported suffering signs of depression, which can potentially result in serious consequences, specifically self-inflicted damage. Although the present study is not statistically generalizable to a broader population, the results are suitable and relevant for educational institutions that prepare doctoral students for rich and meaningful experiences in their doctoral journey. To the best of the authors’ knowledge, this study is among the very few studies that unfold the experiences among doctoral students in higher institutions using a customer journey map while building upon a self-regulation model of a behaviour feedback loop. It shows how higher education institutions should ensure what is offered meets the demands and preferences of students while considering their contemporary needs and wants. These institutions should extend their view beyond the immediate goals of their students to identify relevant touchpoints and other customer journeys that affect the students’ experience.